Use Tableau prep to join datasets together the way you want to - Allchin, Carl (O'Reilly Media, Inc., 2024)
Tableau is one of today's most powerful business intelligence analytics and data visualization tools. It empowers people across the organization to see and understand data for better business decision-making. These Shortcuts will provide you with simple tips and tricks for creating charts, dashboards, and stories that turn data into actionable insights.
Keywords: Tableau (Computer file); Information visualization -- Computer programs; Visual analytics -- Computer programs; Visualisation de l'information; Logiciels; Analyse visuelle; Logiciels